Diagnostic and assessment models patterns - Maria Cristina Núñez Martínez; Felicia Margarita Llerena Bermúdez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
A bibliographic review was carried out about the professional competence assessment of human resources in the Health System and the main characteristics of different models that contribute to their improvement, establishing direct links with the present context of National Health System in Cuba. We include trends and common practices related with assessment models, highlighting those aspects associated with professional competence assessment and its inclusion in the dynamic of a strategy to increase the quality of human resources in Health Services. It has been proved that the appropriate assessment of competences among these professionals assures, through its results, to make valuable decisions on the need of knowledge associated with skills and attitudes that should be present in their daily professional practice.